2015
DOI: 10.1021/jacs.5b03410
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Details of Pd(II)-Catalyzed C–H Iodination with Molecular I2: Oxidative Addition vs Electrophilic Cleavage

Abstract: Transition metal-catalyzed C-H bond halogenation is an important alternative to the highly utilized directed-lithiation methods and increases the accessibility of the synthetically valuable aryl halide compounds. However, this approach often requires impractical reagents, such as IOAc, or strong co-oxidants. Therefore, the development of methodology utilizing inexpensive oxidants and catalyst containing earth-abundant transition metals under mild experimental conditions would represent a significant advance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 127 publications
0
57
0
1
Order By: Relevance
“…However, the method also suffers from a limitation as it provides bis‐iodinated products when both the ortho positions are unsubstituted. The mechanistic investigation carried out by Yu et al14 regarding the CH iodination with molecular I 2 revealed that the iodination could take place via either an oxidative addition or an electrophilic cleavage pathway depending on (i) the extent of interaction between metal and directing group and (ii) the nature of the CH bond [C( sp 3 )H vs. C( sp 2 )H]. Theoretical calculations revealed that a strong directing group donor ability favors the oxidative addition pathway.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the method also suffers from a limitation as it provides bis‐iodinated products when both the ortho positions are unsubstituted. The mechanistic investigation carried out by Yu et al14 regarding the CH iodination with molecular I 2 revealed that the iodination could take place via either an oxidative addition or an electrophilic cleavage pathway depending on (i) the extent of interaction between metal and directing group and (ii) the nature of the CH bond [C( sp 3 )H vs. C( sp 2 )H]. Theoretical calculations revealed that a strong directing group donor ability favors the oxidative addition pathway.…”
Section: Methodsmentioning
confidence: 99%
“…D regenerates the catalyst by releasing the product 3a . However, a redox‐neutral process via an electrophilic cleavage pathway cannot be ruled out 14. In such a case, complex B will coordinate with iodine and then electrophilic attack on the NiC bond occurs by II to yield ionic complex G which further rearranges to the thermodynamically favored D .…”
Section: Methodsmentioning
confidence: 99%
“…[154][155][156][157][158][159] TheR h III -catalyzed C À Hb romination or iodination of benzamides with N-bromosuccinimide (NBS) or Niodosuccinimide (NIS), respectively was reported by Glorius and co-workers (Scheme 47 a). Major progress in CÀHh alogenation was achieved by using various electrophilic halogenating reagents,although in afew cases ad ihalogen (e.g.I 2 )w as used as the halogen source.…”
Section: Halogenationmentioning
confidence: 97%
“…The mechanism of this transformation was later studied computationally by these authors in collaboration with the Musaev group. 140 In 2013, Yu and co-workers contributed the first example of an asymmetric C−H iodination via the desymmetrization of diarylmethylamines (Scheme 51). 141 By employing the chiral monoprotected amino acid (MPAA) ligands developed in their laboratory, they were able to obtain exquisite enantioselectivities of the chiral iodinatined diarylmethylamine products.…”
Section: Scheme 32 Pd-catalyzed Ortho-selective C−h Halogenation Of mentioning
confidence: 99%